Development of a Multidisciplinary Collaboration Model for Inclusive Education Implementation in Kindergarten Settings - Rowiyah, Siti; Hermanto, Hermanto (Journal of Innovation and Research in Primary Education, 2025)
Effective inclusive education for children with special needs requires systematic collaboration among multiple stakeholders. This study developed and validated a multidisciplinary collaboration model to enhance inclusive education implementation in kindergarten settings through structured coordination between teachers, therapists, and parents. This Research and Development study employed the ADDIE framework (Analysis, Design, Development, Implementation, Evaluation) conducted at TK Masyitoh, East Kutai Regency, in February 2025. Three kindergarten teachers participated as end-users. Data collection utilized observation, interviews, and questionnaires. Validation involved material experts, media experts, and instrument validators. Model effectiveness was assessed using normalized gain (N-Gain) analysis comparing pre-implementation and post-implementation teacher performance scores. Expert validation demonstrated high feasibility with material expert scores of 94.4% and media expert scores of 86.6%, both categorized as "highly feasible." Effectiveness assessment revealed significant improvements in teacher competencies, achieving an average N-Gain of 0.89, indicating high-level effectiveness. All participating teachers demonstrated substantial performance improvements following model implementation. The validated model addresses critical gaps in inclusive education implementation by providing systematic guidance for multidisciplinary coordination. Results align with established collaboration theories and support international research emphasizing stakeholder integration in inclusive education. The model's effectiveness demonstrates potential for enhancing teacher preparedness and inclusive education quality in early childhood settings.